Clinical significance of the m6A methyltransferase METTL3 in peripheral blood of patients with coronary heart disease - Chang, Jianshe; Shao, Rui; Xu, Xiangshan; Jin, Yuanzhe (Frontiers in Cardiovascular Medicine, 2024)
Objective: This study aims to explore the association of methyltransferase-like protein 3 (METTL3) expression with severity of coronary artery stenosis in patients with coronary heart disease (CHD). Methods: A total of 100 patients administrated in the Fourth Affiliated Hospital of China Medical University between October 2022 and June 2023 with primary symptoms of chest pain or tightness, or cardiac discomfort, and who underwent coronary angiography for a definitive diagnosis, were included in the study. The baseline characteristics, including TG, TC, LDL-C, HDL-C, uric acid and past history were recorded. Peripheral blood samples were collected to assess the expression levels of METTL3, YT521-B homology domains 1 (YTHDF1), YT521-B homology domains 2 (YTHDF2), and YT521-B homology domains 3 (YTHDF3) using the PCR method. Relative expression levels of METTL3 protein were determined by WB. Correlation analysis were conducted to evaluate the relationship between METTL3/YTHDF1 gene expression and clinical data. Receiver operating characteristic (ROC) curve analysis was employed to assess the predictive value of METTL3 and YTHDF1 for CHD. Binary logistic regression was used to determine whether the expression of METTL3 and YTHDF1 in peripheral blood were risk factors for CHD. Results: The study found no significant differences in baseline characteristics between CHD patients and controls, except for length of stay, Lymphocytes, Neutrophils, AST, HDL-C and modified Gensini score. The gene expression levels of METTL3 and YTHDF1 were significantly higher in CHD patients compared to controls. Furthermore, METTL3 protein expression was also significantly elevated in the CHD group compared to the control group (p < 0.05). METTL3 gene expression correlated with HDL-C and Gensini score, while YTHDF1 gene expression correlated with Age, WBC, Neutrophils, RDW-CV, modified Gensini score. ROC curve analysis demonstrated an AUC of 0.692 for METTL3 in CHD, with a sensitivity of 66.7% and a specificity of 69.8% at a cut-off value of > 0.052. The AUC for YTHDF1 in CHD was 0.623, with a sensitivity of 47.4% and a specificity of 74.4% at a cut-off value of > 0.027. Binary logistic regression revealed that only increased METTL3 expression in peripheral blood was an independent risk factor for CHD (p < 0.05).